2008
DOI: 10.1016/j.cca.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Performance of iohexol determination in serum and urine by HPLC: Validation, risk and uncertainty assessment

Abstract: Background: Determination of glomerular filtration rate plays an important role in nephrological practice. Iohexol is a reference marker for glomerular filtration rate determination. It is available and safe. The aim of this study was to develop a simple, efficient and easy to use analytical method for the quantification of iohexol in serum and urine by high performance liquid chromatography and to thoroughly validate this method. Methods: The HPLC method was inspired from the method published by Krutzen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 25 publications
3
53
0
2
Order By: Relevance
“…This analysis of the supernatant was done on an HPLC system with a diode-array detector (Hitachi, Mannheim, Germany) and a Chromolith performance HPLC column (RP-18e [100 × 4.6 mm], Merck, Darmstadt, Germany) and a Chromolith guard-column (RP-18e [5 × 4.6 mm], Merck) (24,25). Glomerular filtration rate was calculated with the clearance computed from the amount of the marker administered and the area under the receiver-operating characteristic curve of plasma concentration versus time.…”
Section: Iohexol Samplesmentioning
confidence: 99%
“…This analysis of the supernatant was done on an HPLC system with a diode-array detector (Hitachi, Mannheim, Germany) and a Chromolith performance HPLC column (RP-18e [100 × 4.6 mm], Merck, Darmstadt, Germany) and a Chromolith guard-column (RP-18e [5 × 4.6 mm], Merck) (24,25). Glomerular filtration rate was calculated with the clearance computed from the amount of the marker administered and the area under the receiver-operating characteristic curve of plasma concentration versus time.…”
Section: Iohexol Samplesmentioning
confidence: 99%
“…Globally, the performance of 51 Cr-EDTA is good. Chantler, in 1969, showed that results of urinary clearance of 51 Cr-EDTA was within 5% of the results of inulin (Chantler et al, 1969). This excellent concordance between urinary clearances of 51 Cr-EDTA and inulin will be later confirmed by Froissart.…”
Section: Clinical Datamentioning
confidence: 75%
“…As we have shown, iohexol measurements by HPLC are sensitive, specific and reproducible (Back et al, 1988c;Farthing et al, 2005;Cavalier et al, 2008). The high performance of such dosage notably enables the use of iohexol low doses and the measurement on finger-prick samples (Krutzen et al, 1990;Niculescu-Duvaz et al, 2006;Mafham et al, 2007;Cavalier et al, 2008;Aurell, 1994). Iohexol measurement is also pretty stable at room temperature and at -20°C (Krutzen et al, 1984;O'Reilly et al, 1988).…”
Section: Physiological and Analytical Datamentioning
confidence: 92%
See 2 more Smart Citations